Neurological Assessment Using a Physical-Virtual Patient (PVP). (December 2020) - Gonzalez, Laura; Daher, Salam; Welch, Greg
Background. Simulation has revolutionized teaching and learning. However, traditional manikins are limited in their ability to exhibit emotions, movements, and interactive eye gaze. As a result, students struggle with immersion and may be unable to authentically relate to the patient . Intervention. We developed a new type of patient simulator called thePhysical-Virtual Patients (PVP) which combines the physicality of manikins with the richness of dynamic visuals. The PVP uses spatialAugmented Reality to rear project dynamic imagery (e.g., facial expressions, ptosis, pupil reactions) on a semi-transparent physical shell. The shell occupies space and matches the dimensions of a human head. Methods. We compared two groups of third semester nursing students (N=59) from a baccalaureate program using a between-participant design, one group interacting with a traditional high-fidelity manikin versus a more realistic PVP head. The learners had to perform aneurological assessment . We measured authenticity, urgency, andlearning . Results. Learners had a more realistic encounter with the PVP patient (p=0.046), they were more engaged with the PVP condition compared to the manikin in terms of authenticity of encounter and cognitive strategies. The PVP provoked a higher sense of urgency (p=0.002). There was increased learning for the PVP group compared to the manikin group on the pre and post-simulation scores (p=0.027). Conclusion. Therealism of the visuals in the PVP increasesauthenticity and engagement which results in a greater sense of urgency and overall learning.